(3GdHVGYI GdeRLGIs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ceG gh Cgdg hCTcQg hGdTcQ efg cdg (B... (3GdeLdS GdChd aj JMbjb eYfi GdfaS GdEfSGfjI heQGJHgG, bGd YR ef bGFd aj cJGHg GdeLjO(B: (3hfaS heG ShGgGs
(3BNQgG (B:s
(3BNQgG(B: (3hcPdc NjQ hdOg GdMSjf jhe YGThQGA Hjf GdfUQ Ydi CYOGFg hdbGA QHg aGNJGQ dbGA QHg aGHGM fMQg dHjV GdUaGM hUOQg dWYf SeQ GdQeGM aghi Ydi YaQ GdUYjO (B.. (3JMJ GdSjha HMOgG GdeSfhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B3: 71s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs